RELATIVE DATA SAMPLING OF HYPSOMETRIC RELATIONSHIP IN THE SAVANNA REGION OF TOCANTINS - SANTOS, Mayronne Joaquim Fonseca dos; ANDRADE, Valdir Carlos Lima de; SOUZA, Priscila Bezerra de (Brazilian Journal of Biometrics, 2016)
This study aimed to evaluate different sampling systems of hypsometric relationship data in a Savanna area situated in northeastern Tocantins State, Brazil. To this end, 13 plots with an area of 1000 sq m each were used, in which, five simulations of sampling systems were applied for adjustment of the following hypsometric models: Ln(h)=b0+b1(1/d)+Ln(e) and Ln(h)=b0+b1(N)+b2(dq/d)+b3(1/d)+Ln(e). These models had coefficient of determination ranging from 0.419 to 0.509 and standard error of estimate from 27.66% to 29.75%. From a completely randomized design in a split plot scheme, with subsequent application of Dunnett test, both at the level of 0.05, the study revealed that the sampling system with 50% of the trees in each plot produced the best equations of height (h) according to the diameter at breast height (d), quadratic diameter (dq) and number of specimens per hectare (N).